Development of an e-teaching tool for revolving vane compressor - He, Zhongjie. (2009)
ABSTRACT Energy-saving and environment protection have become the key theme for manufacturers in today’s compressor industry. Positive-displacement compressors with higher mechanical efficiency (i.e. less frictional losses and thus more energy efficient) are preferable for both refrigeration and air conditioning applications. This report presents both the design work for mechanical efficiency improvement, and the development of an E-learning tool for positive displacement compressor with user friendly user interface (UI).